EPISTEMOLOGI ILMU DALAM AL-QUR’AN - Lubis, Agus Salim (IAIN PADANGSIDIMPUAN, 2013)
AbstrakAl-Quran as the words of God revealed to the Prophet Muhammad become a way of life to man is not only to teach about faith, worship, laws and morality, but the Quran also describes about things related to science. In the Quran there is the term al-nazhr, al-fikr,al-aql, and al-qalb which suggests some form of scientific methodology. Scientific methodology revealed this Quran has been practiced by the scientists and philosophers, the method of observation(al-nazhr), method of rational thinking(al-fikrand al-aql), as well as intuitive method(al-qalb). But according to the Quran, the use of these methods is to get the truth in order to strengthening the faith(dzikrullah).Kata kunci :al-Nazhr, al-Fikr, al-Aql, dan al-Qalb.